Influence of Endodontic Procedure on Postoperative Pain - Evidence from Systematic Reviews - Krunić Jelena; Mladenović Irena; Žuža Aleksandra; Radović Igor; Stojanović Nikola (Balkan Stomatological Society, 2019)
Pain control, during and after root canal treatment is one of the important issues in endodontic practice. Occurrence of pain after intervention often presents considerable distress to both patient and dentist. In many studies influence of different endodontic treatment factors on incidence of postoperative pain has been investigated. However, different and inconsistent results between studies and growth in number of published papers each year made professional updating and clinical-decision making challenging. Systematic reviews synthesized and combined data from relevant studies to find the answer to a research question providing the highest level of scientific evidence. Thus, their use may facilitate decision making in clinical practice. The aim of this article was to present results from systematic reviews about the influence of endodontic treatment on postoperative pain.